Triz as a support methodology for new product development - Dias, Ana (2019)
Growing demands and rapid changes in markets compel organizations to think more about innovation and continuous improvement. Nowadays, any growth strategy, and even its own survival in the markets, is increasingly being applied by new approaches and management methodologies. The study developed in the scope of this paper focused on the approach and interpretation of the use of the TRIZ methodology, in search of new ways of solving problems, identifying their support tools. Another concept explored and related to TRIZ is the New Product Development (NPD). The present paper aims to approach the concept of TRIZ regarding NPD and the way they are related by following innovative doctrines appealing to creativity. Within this paper and through the analysis of the different fields investigated, a diagrammatic model was proposed contemplating concepts and relations between them. In order to analyze the feasibility of the implementation of this same diagrammatic model in an industrial environment, a case study was presented in a company that uses TRIZ, and through a conclusive analysis, it is verified that the proposed model can be used as support in solving problems of an innovative and creative nature inherent to the implementation of new management processes and their improvement.